2022
DOI: 10.1136/svn-2022-001677
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial thrombolytics during endovascular thrombectomy for acute ischaemic stroke in the MR CLEAN Registry

Abstract: IntroductionThe efficacy and safety of local intra-arterial (IA) thrombolytics during endovascular thrombectomy (EVT) for large-vessel occlusions is uncertain. We analysed how often IA thrombolytics were administered in the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) Registry, whether it was associated with improved functional outcome and assessed technical and safety outcomes compared with EVT without IA thrombolytics.MethodsIn this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A previous meta-analysis including 4581 patients by Chen et al 10 reported that IA treatment (thrombolytics or glycoprotein IIb/IIIa inhibitors) was associated with a higher rate of functional independence and another meta-analysis including 2797 patients by Kaesmacher et al 11 reported that IAT was not associated with higher rates of functional independence as an adjunct to MT. Inclusion of additional studies 5,[12][13][14][15][16][17] such as results from the randomized CHOICE 17 trial in our analysis increased the sample size (7572 patients) by almost 2-4 folds compared with the previous analyses by Chen et al 10 and Kaesmacher et al 11 Therefore, the precision of estimates of various outcomes was higher, and type 2 errors in comparisons were reduced. By increasing the design diversity among included studies, we also identified the prominent effect of design and quality of the studies on the association between IAT and functional independence at 90 days.…”
Section: Salient Findingsmentioning
confidence: 77%
See 3 more Smart Citations
“…A previous meta-analysis including 4581 patients by Chen et al 10 reported that IA treatment (thrombolytics or glycoprotein IIb/IIIa inhibitors) was associated with a higher rate of functional independence and another meta-analysis including 2797 patients by Kaesmacher et al 11 reported that IAT was not associated with higher rates of functional independence as an adjunct to MT. Inclusion of additional studies 5,[12][13][14][15][16][17] such as results from the randomized CHOICE 17 trial in our analysis increased the sample size (7572 patients) by almost 2-4 folds compared with the previous analyses by Chen et al 10 and Kaesmacher et al 11 Therefore, the precision of estimates of various outcomes was higher, and type 2 errors in comparisons were reduced. By increasing the design diversity among included studies, we also identified the prominent effect of design and quality of the studies on the association between IAT and functional independence at 90 days.…”
Section: Salient Findingsmentioning
confidence: 77%
“…The quality of included observational studies 5,6,[12][13][14][15][16][20][21][22][25][26][27][28][29][30][31] was assessed by three independent reviewers (A.L., I.N.A., and D.K.) for risk of bias using the Newcastle-Ottawa Quality Scale (NOS) for Cohort Studies.…”
Section: Risk Of Bias Assessment In Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have yielded conflicting results: some have indicated that IVT is a predictor of FR [8,28,29], while others have suggested that IVT may have protective effects [9,[30][31][32]. Furthermore, some studies have reported the minimal impact of thrombolytic therapy on the development of FR [33][34][35][36][37].…”
Section: Rationale and Development Of A Futile Recanalization Risk Scorementioning
confidence: 99%